Film genre and representation of African migration : a study of selected expository documentaries - Mashiane, Patricia Phindile (My University, 2024)
The study examines three African migration documentary films, namely Inside the world’s deadliest migrant route (2021), African migrants: What really drives them to Europe (2015) and Shattered dreams of African migrants (2020) and how they represent African migration, particularly on their dangerous journeys to Western Europe. The objectives were to analyse the narrative focus of documentary films on African migration, explore the depiction of African migrants’ experiences, determine the ideological frames used to portray African migration, and establish the relevance of the genre in depicting economic and political issues relating to African migration. Framing theory and Neoclassical theory of migration were used to underpin the study whereas the qualitative descriptive case study design, purposive sampling and content analysis were applicable in executing the study process including data collection. Study findings were generated through a step-by-step thematic content analysis procedure where it was noted that push factors such as poverty, conflict, and untenable health care conditions in Africa compel migrants to leave their countries. This is compounded by a number of pull factors such as perceived employment opportunities, stable security and safety systems, quality education and healthcare that attract poor Africans to the receiving countries. The study further noted several ideological frames used to present African migration as a humanitarian crisis where desperate journeys are depicted within different media frames. These include the intruder and illegal person frames; helpless-victim frame, economic burden frame, and other frames that often that depict migrants in a prejudiced, and dehumanizing manner.
Thesis (M. (Media Studies)) -- University of Limpopo, 2024
Keywords: Africa; Migrants; Western Europe; Representation; Documentary; Immigrants; Documentary films; Film genres; Immigrants -- Africa